2023
DOI: 10.1109/tpami.2022.3186876
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Detect 3D Symmetry From Single-View RGB-D Images With Weak Supervision

Abstract: 3D symmetry detection is a fundamental problem in computer vision and graphics. Most prior works detect symmetry when the object model is fully known, few studies symmetry detection on objects with partial observation, such as single RGB-D images. Recent work addresses the problem of detecting symmetries from incomplete data with a deep neural network by leveraging the dense and accurate symmetry annotations. However, due to the tedious labeling process, full symmetry annotations are not always practically ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Prior works of symmetry detection are only applicable to synthetic objects in the virtual world, limiting the effectiveness of robotic applications. Several recent works studies detecting symmetry from partially observed data with various formats, such as RGB image [42], RGB-D image [32], [33], and 3D volume [10]. Our method is inspired by the above methods.…”
Section: B Symmetry Detectionmentioning
confidence: 99%
“…Prior works of symmetry detection are only applicable to synthetic objects in the virtual world, limiting the effectiveness of robotic applications. Several recent works studies detecting symmetry from partially observed data with various formats, such as RGB image [42], RGB-D image [32], [33], and 3D volume [10]. Our method is inspired by the above methods.…”
Section: B Symmetry Detectionmentioning
confidence: 99%
“…Another approach is to create a synthetic categorization task where one can create a surrogate class by altering a single image multiple times through translations, color shifts, and rotations [46]. Furthermore, in [47], in order to detect 3D symmetry from single-view RGB-D images, the author uses weak supervision to detect objects.…”
Section: Related Workmentioning
confidence: 99%
“…The geographic information system and the advancement of artificial intelligence (AI) technology will promote the development of more efficient and accurate studies on the sensitivity of the landslide inventory, which makes the evaluation of contributing factor system more reasonable (Ghorbanzadeh et al, 2022b). More intelligent models are applied to landslide susceptibility, and all kinds of machine learning methods, including logistic, classification and regression tree (CART), SVM, and transfer learning, have been widely used (Huo et al, 2019;Ghorbanzadeh et al, 2022c;Shi et al, 2022;Wang et al, 2022). C5.0 decision tree, random forest, and support vector machine are used to partition landslide sensitivity and compare its performance in the coal mining area.…”
Section: Introductionmentioning
confidence: 99%